Decentralisation, Village Autonomy, and Equitable Rural Development in Indonesia: A Conceptual Study of Authority, Fiscal Capacity, and Accountability - Radfan Faisal (Universitas Muhammadiyah Jakarta, 2024)
Decentralisation has become a central pillar of Indonesia’s post-reform governance architecture, particularly in strengthening regional autonomy and improving public service delivery at the local level. Within this framework, village autonomy occupies a strategic position because villages are the closest governmental units to rural communities and are expected to translate national development priorities into locally responsive programmes. This article examines the implementation of decentralisation in village autonomy as an institutional mechanism for promoting equitable rural development in Indonesia. Using a normative-juridical and conceptual research design, this study analyses statutory provisions, policy documents, and relevant academic literature on village authority, village finance, and governance accountability. The findings indicate that village autonomy has been institutionally strengthened through legal recognition, fiscal transfers, and the delegation of authority to villages. However, its effectiveness remains constrained by administrative capacity, uneven human resources, limited planning competence, regulatory complexity, and weak accountability mechanisms in some local contexts. The study argues that village autonomy can contribute meaningfully to development equity only when legal authority, fiscal capacity, participatory planning, and multi-layered supervision operate as an integrated governance system. The article concludes that decentralisation at the village level should not be understood merely as the transfer of authority and funds, but as a transformative governance process requiring institutional capacity, community participation, transparency, and accountable leadership.